Results of the gas carrier reliquefaction plant trial - Miliajev, Viktor; Erlihman, Vladimir; Fatyhov, Yury (Transport, 2007)
In the paper results of the gas carrier reliquefaction plant trial are considered. Safe transportation of liquefied gases is explained. The construction of the ship on trial is described. Designed parameters of the reliquefaction plant are presented. Heat gain into cargo tanks is obtained. Volumetric capacity, cooling capacity, volumetric efficiency and power consumption of the compressors are determined. Results of the main engine trial, diesel generator trial, reliquefaction plant trial, and calculations performed afterwards are represented in five tables. The results obtained may be used for optimisation calculations of gas carriers’ reliquefaction plants.First Published Online: 27 Oct 2010